Physical and technological aspects of multicharge implantation of gallium arsenide in device and circuit structures - Новосядлий, Степан Петрович; Кіндрат, Тарас Петрович; Мельник, Любомир Васильович (Eastern-European Journal of Enterprise Technologies, 2013)
The development of microelectronics in Ukraine was accompanied by altering of four generations of ion implantation equipment. Nowadays, ion implantation devices of three classes of small and medium doses, high doses and high energies, are used for micro-, opto- and nanoelectronics. For many years, double-chamber ’’Vezuviy-3’’ and its modified version ’’Vezuviy-3M’’, with drum-type receiving units and electrostatic ion beam scanning, have been the most popular among light-dose devices. Despite its reasonable price, it has high efficiency (300 plates mm per hour), high implantation heterogeneity ( over a plate) and performance reliability (availability factor was). High dose devices ’’Vezuviy-4’’ and ’’Vezuviy-8’’ of the 70-80s and their modified versions, with combined mechanical and electro-magnetic scanning, were produced using ion beam post-acceleration and receiving unit, which was both at high and ground potentials. The development of high-energy implantation was based on using multi-charge ions (2-4) of the main dopants. The energies below 2 MeB at total accelerating voltage 400 KeB and ion beam current below 1mА and below 0,3 mА were recorded in one of modified versions of high-energy implantation ’’Vezuviy-9’’. It was the starting point of decreasing radiation defects in BIC structures.